1999
DOI: 10.1577/1548-8659(1999)128<0001:ecomlh>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Correlates of Male Life History Variation among Coho Salmon Populations from Two Oregon Coastal Basins

Abstract: Documenting the spatial scale and possible causes of life history variation among populations of coho salmon Oncorhynchus kisutch can improve ecological understanding and guide efforts to conserve potentially adaptive intraspecific diversity. In this paper I use 14 years of spawning ground survey data for 10 populations from the Coos and Coquille basins on the southern Oregon coast to examine interpopulation differences in the proportion of males that spawn as 2year-old jacks instead of as 3-year-old adults. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 64 publications
2
19
0
Order By: Relevance
“…Second, similar degrees of intercohort variation in the probability of early maturation have been observed under other sampling and observation schemes. For example, Young (1999) and Vøllestad et al (2004) observed levels of variability similar to those reported here, and much of their data were developed by classifying fish on the basis of length (early-maturing males are short) rather than from tagbased estimates of age. Third, Snover et al (2006) show that changes in the distribution of prey resources at sea may cause the probability of early maturation to span orders of magnitude.…”
Section: Probability Of Coho Salmon Early Maturationsupporting
confidence: 57%
See 2 more Smart Citations
“…Second, similar degrees of intercohort variation in the probability of early maturation have been observed under other sampling and observation schemes. For example, Young (1999) and Vøllestad et al (2004) observed levels of variability similar to those reported here, and much of their data were developed by classifying fish on the basis of length (early-maturing males are short) rather than from tagbased estimates of age. Third, Snover et al (2006) show that changes in the distribution of prey resources at sea may cause the probability of early maturation to span orders of magnitude.…”
Section: Probability Of Coho Salmon Early Maturationsupporting
confidence: 57%
“…The strength of regional variation in the probability of early maturation provides new perspectives on results reported by Young (1999). Young (1999) found that interpopulation variation in the probability of early maturation by male coho salmon from 10 streams in 2 basins was best explained by stream-level, rather than basin-level, environmental conditions. Young's (1999) study area was within one of our regions (region 2), and his two basins correspond to our basins 4 and 5.…”
Section: Spatial Variation In the Probability Of Early Maturationmentioning
confidence: 86%
See 1 more Smart Citation
“…What is the variation of condition in a school/cohort/population, and does this variation change relative to environment? Do tuna spectrum early into potential breeders and non-breeders, as has been demonstrated for salmon (Young, 1999;Hobday and Boehlert, 2001)? A "condition-survival relationship" could support management and conservation strategies.…”
Section: Benefits Of Knowing the Condition Of Tagged Fishmentioning
confidence: 99%
“…Demonstrating the dynamics of alternative phenotypes associated with environmental variation, however, has received less empirical attention (but see Young 1999; Healey, Henderson & Burgetz 2000). Using spawning survey data, Young (1999) showed that the proportion of O. kisutch jacks varied within and among streams from two neighbouring river basins, and that the among‐stream variation was related to variation in local demographic (i.e. density) and environmental conditions (stream gradient, elevation and distance to the bay).…”
Section: Introductionmentioning
confidence: 99%